2016
DOI: 10.18356/140e2e2d-en
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unfair inequality in Brazil, 1995 and 2009

Abstract: This article analyses the trend of unfair inequality in Brazil (1995-2009) using a nonparametric approach to estimate the income function. The entropy metrics introduced by Li, Maasoumi and Racine (2009) are used to quantify income differences separately for each effort variable. A Gini coefficient of unfair inequality is calculated, based on the fitted values of the non-parametric estimation; and the robustness of the estimations, including circumstantial variables, is analysed. The trend of the entropies dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In the analysis for Brazil, Annegues et al (2015) also find divergences between the trends shown by traditional measures of inequality and measures of opportunity inequality. The authors calculated indices of entropy between 1995 and 2009 and found that measures of IOp in the country remained stable, with effort accounting for approximately 0.19, using the parametric method, and 0.21, using the non-parametric method.…”
Section: Review Of the Literaturementioning
confidence: 85%
See 1 more Smart Citation
“…In the analysis for Brazil, Annegues et al (2015) also find divergences between the trends shown by traditional measures of inequality and measures of opportunity inequality. The authors calculated indices of entropy between 1995 and 2009 and found that measures of IOp in the country remained stable, with effort accounting for approximately 0.19, using the parametric method, and 0.21, using the non-parametric method.…”
Section: Review Of the Literaturementioning
confidence: 85%
“…The non-parametric method requires a greater number of observations in the sample, with a positive bias when we subdivide the sample into groups of circumstances with few observations. As shown in the literature, the discrepancies between the parametric and non-parametric is that the non-parametric methods tend to yield higher values of IOp than the parametric ones (Ferreira and Gignoux, 2011; ANNEGUES et al , 2015). To estimate the lower-bound IOp, the parametric method is seen as an adequate approach (Bourguignon et al , 2007; Ferreira and Gignoux, 2011).…”
Section: Methodsmentioning
confidence: 95%